Oral submucous fibrosis in Durban, Natal : a study of its epidemiology, aetiology and morphological features - Seedat, H. A.(Hoosen Ahmed) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.(Odont.)) -- University of Stellenbosch, 1985.